2014
DOI: 10.1089/end.2014.0226
|View full text |Cite
|
Sign up to set email alerts
|

First Prize: Evaluation of the Tensile Strength of the Human Ureter—Preliminary Results

Abstract: The circumferential tensile strength of the ureter was found to be significantly lower than the longitudinal strength. Circumferential tensile strength was also lower with more proximal parts of the ureter. This information may be important for the design of "intelligent" devices and simulators to prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…13,14 The reasons for this difference may be an increased need for manipulation and auxiliary equipment, and working in a relatively weaker and narrower segment of the ureter. In addition, in recent experimental study, Shilo and colleagues 22 reported that the proximal ureter had less tensile strength, and complications tended to occur more in this part of ureter.…”
Section: Ureteroscopy In Proximal Ureteral Stonesmentioning
confidence: 97%
“…13,14 The reasons for this difference may be an increased need for manipulation and auxiliary equipment, and working in a relatively weaker and narrower segment of the ureter. In addition, in recent experimental study, Shilo and colleagues 22 reported that the proximal ureter had less tensile strength, and complications tended to occur more in this part of ureter.…”
Section: Ureteroscopy In Proximal Ureteral Stonesmentioning
confidence: 97%
“…But observance of intense inflammation in the ureter during ureteroscopy is among the important factors [15]. The presence of inflammatory tissue in proximal or distal ureter or the region where the stone was impacted forms a potential for ureteral wall rupture [16]. Added to this factor, the delicate tensile strength of the region was stated as 457.52-3374 N cm −2 in circumferential direction and as 902.43-122.08 N cm −2 in the longitudinal direction [16].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of inflammatory tissue in proximal or distal ureter or the region where the stone was impacted forms a potential for ureteral wall rupture [16]. Added to this factor, the delicate tensile strength of the region was stated as 457.52-3374 N cm −2 in circumferential direction and as 902.43-122.08 N cm −2 in the longitudinal direction [16]. In our cases, the ureter, especially its distal end, was observed to be inflamed.…”
Section: Discussionmentioning
confidence: 99%
“…As seen from Figure , the rate of deformation in the ureter wall, which is an anisotropic hyperelastic material, is transferred to the fluid domain due to the FSI coupling and generates a complex flow pattern in the bolus, which could not be generated if only the fluid domain were considered or the ureter wall was modeled as a rigid surface. Also, the values of von Mises stress plotted in Figures and showed that the maximum value of the von Mises stresses was found to be around 2.5 MPa, which is well below the maximum stress of 4.1 MPa, a human ureter can withstand before failure, as reported by Shilo et al For improving convergence, the initial bulk modulus was chosen to be very high, thereby modeling it as a nearly incompressible material, a common practice for these kinds of nonlinear FSI simulations. …”
Section: Discussionmentioning
confidence: 99%